RUSSIA’S CONTRIBUTION TO THE ESTABLISHMENT OF A LIMITED MONARCHY IN SERBIA (1808-1838) - Чворовић, Зоран Р (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
This paper is dedicated to the role and views of official Russia in the process of establishing the system of government in Serbia, from the Erfurt Convention of 1808 to the Hatt-i-Sharif of 1838. The central issue discussed in the paper, based primarily on historical sources and recent literature, is Russia’s role in the establishment of a limited monarchy in Serbia after the Second Serbian Uprising. The author has chosen to investigate this issue primarily due to the diametrically opposed assessments in Serbian legal and historical science regarding Russia’s role in the constitutional development of Serbia during the first four decades of the 19th century. Starting from the thesis that Russia’s advocacy for the introduction of a Council with permanent members was crucial for the establishment of a limited monarchy and the opening of the constitutional question in Serbia, the author demonstrates, based on archival material, that such advocacy was part of the long-term strategy of Russian foreign policy at the time. This refers to the policy of "constitutional diplomacy" of Tsar Alexander I. The author further shows that the fundamental principles of this policy did not change with regard to Serbia, even after Tsar Alexander I and his successor Nicholas I officially abandoned this policy. The paper offers a different view of Russia’s stance toward the Sretenje Constitution than that which dominates in Serbian social sciences. The Russian protest against the Sretenje Constitution is linked to the contemporary policy of maintaining a "weak neighbor" pursued by official St. Petersburg in relation to the Ottoman Empire, as well as to Russia’s consistent support for the introduction of a limited monarchy in Serbia, which was hindered by the Sretenje Constitution.